Structure based design and syntheses of amino-1H-pyrazole amide derivatives as selective Raf kinase inhibitors in melanoma cells - Kim, Mi-hyun; Kim, Minjung; Yu, Hana; Kim, Hwan; Yoo, Kyung Ho; Sim, Taebo; Hah, Jung-Mi (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The synthesis of a novel series of N-(5-amino-1-(4-methoxybenzyl)-1H-pyrazol-4-yl amide derivatives 6a-o, 7a-s and their antiproliferative activities against A375P melanoma cell line were described. Most compounds showed competitive antiproliferative activities to sorafenib, the reference standard. Among them, N-(5-amino-1-(4-methoxybenzyl)-1H-pyrazol-4-yl)-5-(3-(4-chloro-3-(trifluoromethyl)phenyl)ureido)-2-methylbenzamide 7c exhibited potent activities (GI(50) = 0.27 mu M). Especially, 7c was found to be a potent and selective B-Raf V600E and C-Raf inhibitor (IC50 = 0.26 mu M, IC50 = 0.11 mu M, respectively), showing a possibility as melanoma therapeutics. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: BRAF; MUTATIONS; CRAF